Development of a Sports Training Program Planning Information System (SIPRENPOL) - Ibrahim; Syahputra Manik; Siti Rahima Gultom; Nurkadri; Wahyu Eko Widiyanto; Khairul Hamsyah; Syaifullah Yophi Ardiyanto; Ratko Pavlovic (Sport TK)
This study aimed to develop a Sports Training Program Planning Information System (SIPRENPOL) to aid sports trainers in the creation of structured and systematic training programs. The study employed a research and development process. The methodologies used followed the research and development framework. The data analysis included both quantitative and qualitative descriptive techniques to assess and ascertain the viability of the created items. The study involved 75 students, with 15 participating in small-scale trials and 60 in large-scale trials, all from the Sports Coaching Education (PKO) program at the Faculty of Sports Science (FIK), Medan State University.  Instruments and data gathering methods employ media assessment surveys for subject matter experts, media specialists, and students. The findings indicated that the SIPRENPOL enhanced planning efficiency, transparency, and communication in the administration of training programs. This integration demonstrates the advantageous impacts of information technology on sports management. The system can function as a prototype for more sports, enhancing training efficacy and personal growth. Its successful deployment relies on users' comprehension and preparedness to utilize the technology effectively.